Here comes everybody : the power of organizing without organizations - Shirky, Clay, ....- (New York : Penguin Press, 2008)
Blogs, wikis and other Web 2.0 accoutrements are revolutionizing the social order, a development that's cause for more excitement than alarm, argues interactive telecommunications professor Shirky. He contextualizes the digital networking age with philosophical, sociological, economic and statistical theories and points to its major successes and failures. Grassroots activism stands among the winners-Belarus's flash mobs, for example, blog their way to unprecedented antiauthoritarian demonstrations. Likewise, user/contributor-managed Wikipedia raises the bar for production efficiency by throwing traditional corporate hierarchy out the window. Print journalism falters as publishing methods are transformed through the Web. Shirky is at his best deconstructing Web failures like Wikitorial, the Los Angeles Times's attempt to facilitate group op-ed writing. Readers will appreciate the Gladwellesque lucidity of his assessments on what makes or breaks group efforts online: Every story in this book relies on the successful fusion of a plausible promise, an effective tool, and an acceptable bargain with the users. The sum of Shirky's incisive exploration, like the Web itself, is greater than its parts. (Mar.)
It takes a village to find a phone -- Sharing anchors community -- Everyone is a media outlet -- Publish, then filter -- Personal motivation meets collaborative production -- Collective action and institutional challenges -- Faster and faster -- Solving social dilemmas -- Fitting our tools to a small world -- Failure for free -- Promise, tool, bargain -- Epilogue.
Keywords: Computer networks -- Social aspects; Information technology -- Social aspects; Internet -- Social aspects; Ondernemingen -- Organisatie; Online social networks